Análisis de protecciones eléctricas de microgrids modo isla con elevada penetración de energías renovables no convencionales - Ortiz Santiana, Kevin Alexander (2023)
The integration of distributed generation in microgrids offers a renewable alternative to conventional generation with improved power quality and reduced energy losses. However, microgrids also pose new technological challenges such as the coordination of electrical protection measures against short-circuit currents and fluctuations in the bidirectional energy flow. This investigation measures the operating conditions of the load and generation to determine the best settings and protection against overcurrent for microgrids.